Habit tic nail dystrophy: a case report affecting single thumb nail - Oommen, Boby John; Kadori, Waad Ibrahim Majed (International Journal of Research in Medical Sciences, 2020)
Habit-tic deformity is a classic example of overlap between the domains of dermatology and psychiatry. Mostly seen in adults, it results from the habit of picking or pushing the cuticle backward. A case of habit-tic deformity of a single thumb nail is reported and the simple treatment measure adopted discussed.